PMA – Zeolite (Clinoptilolite) in the Management of Irritable Bowel Syndrome – a Non-Interventional Study - Mosgoeller, Wilhelm; Muss, Claus; Eisenwagen, Sandra; Jagsch, Reinhold; Vogelsang, Harald (Zeitschrift für Gastroenterologie, 2024)
In clinical practice, the treatment of patients with irritable bowel syndrome (IBS) can be very challenging. The aims of the present non-interventional study (NIS) were to investigate the tolerability and efficacy of PMA-zeolite under everyday conditions in patients with diarrheic IBS type (IBS-D) or constipated type (IBS-C) or mixed type (IBS-M).Methods To document prospective data on tolerability and symptom frequency in the frame of a nationwide NIS, we recruited 204 IBS patients. The study focused on the IBS-related quality of life (measured by the SF-36 questionnaire) and improvements of IBS-related symptoms according to specific ROM-III criteria and stool consistency (Bristol stool scale). The participants documented their abdominal pain, bloating, number of bowel movements, and stool consistency through a web-based internet platform (initial and exit questionnaires) and daily diary entries over the period of intake (8 weeks).Results A total of 82.2% of the recruited patients had filled in the questionnaires before and after the 8-week treatment with PMA-zeolite. Seven of the eight subscales of the SF-36 improved significantly (p<0,001); the reduction in abdominal pain was especially significant (p<0,001). The diary entries confirmed the reduction in abdominal pain and revealed a significant reduction in days with bloating (p<0,001). The Bristol-stool-scale analysis showed improvements; particularly, patients with IBS-D benefited from the treatment (p<0,001). Conclusion The treatment duration of 8 weeks was well tolerated by most patients. Under everyday life conditions, PMA-zeolite alleviated the global IBS-related symptoms and raised the quality of life (QOL). The PMA-zeolite, thus, may represent a good adjuvant therapeutic option for patients with irritable bowel syndrome.
Keywords: IBS; irritable bowel syndrome; PMA-zeolite as adjuvant remedy; observational (non-interventional) study